2020
DOI: 10.3389/fbuil.2020.00021
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Out of Carbon Lock-In: Malaysia’s Path to Decarbonization

Abstract: Malaysia has made an ambitious commitment to reduce the intensity of its carbon emissions, notably a 40% reduction (compared to 2005 levels) by 2020 and a 45% reduction (compared to 2005 levels) by 2030. As with other developing countries, Malaysia's challenge is to decarbonize its energy-centric economy in the face of population growth pressures and substantial levels of poverty. Drawing on extensive interviews with both public and private stakeholders, we examine how Malaysia has launched its transition to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 8 publications
0
27
0
1
Order By: Relevance
“…The aim was to promote the use of renewable energies in power plants, promoting public transportation, and inspiring the usage of sustainable technologies. According to the Ministry of Energy, Green Technology and Water the greenhouse gas (GHG) emission is projected to decrease by more than 40 percent by 2030 by the successful implementation of the Green Technology Master Plan (Susskind et al, 2020). In 2016 the Malaysian government announced its plan to promote battery electric vehicles in the country (Susskind et al, 2020).…”
Section: Earlier Studies On Intention To Buy Hybrid and Electric Vehiclesmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim was to promote the use of renewable energies in power plants, promoting public transportation, and inspiring the usage of sustainable technologies. According to the Ministry of Energy, Green Technology and Water the greenhouse gas (GHG) emission is projected to decrease by more than 40 percent by 2030 by the successful implementation of the Green Technology Master Plan (Susskind et al, 2020). In 2016 the Malaysian government announced its plan to promote battery electric vehicles in the country (Susskind et al, 2020).…”
Section: Earlier Studies On Intention To Buy Hybrid and Electric Vehiclesmentioning
confidence: 99%
“…According to the Ministry of Energy, Green Technology and Water the greenhouse gas (GHG) emission is projected to decrease by more than 40 percent by 2030 by the successful implementation of the Green Technology Master Plan (Susskind et al, 2020). In 2016 the Malaysian government announced its plan to promote battery electric vehicles in the country (Susskind et al, 2020). An essential advantage of BEVs is to improve the quality of life in terms of environment and health, which especially in urban areas will lead to sustainable transportation enhancement (Pita et al, 2020).…”
Section: Earlier Studies On Intention To Buy Hybrid and Electric Vehiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…As a nation, Malaysia is committed to reducing carbon dioxide emissions and this is “reflected in its Nationally Determined Contribution to the Paris Agreement, i.e. to reduce its emissions intensity by 45% by 2030 (relative to its emissions intensity per unit of GDP in 2005), with 10% of this goal contingent upon international assistance” (Susskind et al , 2020). Not unlike most nations, Malaysia is transitioning to renewable energy to achieve the goal.…”
Section: Research Context Methods and Data Analysismentioning
confidence: 99%
“…The World Economic Forum (2019) reported that developed countries like the United States and Europe have less than 3 percent of electric vehicles and this figure is even lower in other regions. The slow uptake of electric vehicles is mainly explained by behavioral transformation (Susskind et al, 2020). As the emissions are contributed from daily individual activities, the repercussion from the behavioral choices can be reduced by controlling and shifting such behaviors.…”
Section: Introductionmentioning
confidence: 99%